Expertise-dependent visuocognitive performance of chess players in mating tasks: evidence from eye movements during task processing - Küchelmann, Thomas; Velentzas, Konstantinos; Essig, Kai; Schack, Thomas (Frontiers in Psychology, 2024)
Visuocognitive performance is closely related to expertise in chess and has been scrutinized by several investigations in the last decades. The results indicate that experts’ decision-making benefits from the chunking process, perception and visual strategies. Despite numerous studies which link these concepts, most of these investigations have employed common research designs that do not use real chess play, but create artificial laboratory conditions via screen-based chess stimuli and obtrusive stationary eye tracking with or without capturing of decision-making or virtual reality settings. Therefore, the present study assessed the visuocognitive performance of chess novices, intermediates and experts in a real chess setting. Instead of check detection, and find-the-best-move tasks or to distinguish between regions of a chessboard that were relevant or irrelevant to the best move in previous studies, we introduced n-mate tasks and sequentially manipulated their difficulty. Due to the complexity of the tasks, Wwe monitored players’ visual strategies in a fine-graded the initial phase (different time intervals instead of analysing a fixed number of first fixations) of task-solving and for complete trials, employing non-obtrusive mobile eye tracking, multi-sensor observation and full-automatic annotation of decision-making. The results revealed significant expertise-dependent differences in visuocognitive performance. based on a circumstantial spatial and temporal analysis. In order to provide more detailed results, for the first time the analyses were performed under the special consideration of different time intervals and spatial scalings. In summary, experts showed a significantly higher number of fixations on areas of interest and empty squares between pieces in the of task processing. However, they had a strikingly low total number of fixations experts apply different visual search strategies problem-solving. Moreover, experts’ visuocognitive processing benefits from stored chunks of mating constellations.